Leukotriene B4 receptor BLT2 negatively regulates allergic airway eosinophilia. Issue 8 (19th April 2013) - Matsunaga, Yuko; Fukuyama, Satoru; Okuno, Toshiaki; Sasaki, Fumiyuki; Matsunobu, Takehiko; Asai, Yukari; Matsumoto, Koichiro; Saeki, Kazuko; Oike, Masahiro; Sadamura, Yukari; Machida, Kentaro; Nakanishi, Yoichi; et al.
Abstract : Leukotriene B4 (LTB4 ) has been implicated in the pathogenesis of allergic diseases. BLT2, a low‐affinity LTB4 receptor, is activated by LTB4 and 12( S )‐hydroxyheptadeca‐5 Z, 8 E, 10 E ‐trienoic acid (12‐HHT). Although the high‐affinity LTB4 receptor BLT1 has been shown to exert proinflammatory roles, the role of BLT2 in allergic inflammation has not been clarified. To study the function of BLT2 in development of asthma, we used mice model of ovalbumin (OVA)‐induced allergic airway disease. The 12‐HHT levels were elevated in bronchoalveolar lavage (BAL) fluids of OVA‐sensitized/challenged wild‐type mice. BLT2 ‐deficient mice exhibited enhanced eosinophilia in BAL fluids after OVA exposure. Interleukin (IL)‐13 levels in BAL fluids and IL‐13‐producing CD4 + T cells in the lungs were elevated in BLT2 ‐deficient mice compared to wild‐type mice, whereas the levels of IL‐4, IL‐5, and interferon (IFN)‐γ in BAL fluids and serum OVA‐specific IgE were comparable. Transfection of BLT2‐specific small interfering RNA enhanced IL‐13 production in CD4 + T cells in vitro. Expression of BLT2 mRNA in CD4 + T cells was significantly reduced in patients with asthma compared to healthy control subjects. These findings indicate that BLT2 has a protective role in allergic airway inflammation and that diminished BLT2 expression in CD4 + T cells may contribute to the pathophysiology of asthma.—Matsunaga, Y., Fukuyama, S., Okuno, T., Sasaki, F., Matsunobu, T., Asai, Y., Matsumoto, K., Saeki, K., Oike, M., Sadamura, Y., Machida, K., Nakanishi, Y., Kubo, M., Yokomizo, T., Inoue, H., Leukotriene B4 receptor BLT2 negatively regulates allergic airway eosinophilia. FASEBJ. 27, 3306‐3314 (2013). www.fasebj.org